An antecedent of later developing communicative functions: the fetal index finger - Marschik, Peter B; Prechtl, Heinz F R; Prayer, Daniela; Peyton, Colleen; Einspieler, Christa (BMJ (Online), 2013)
Introducing dynamic magnetic resonance imaging (MRI) broke new ground in visualising human fetal behaviour. 1 We use this method for detailed analyses of complex and coordinated fetal motor patterns, to study spontaneous motor activity, and for functional assessments of the young nervous system. 2 While analysing a fetus at 27 weeks of gestation during an uneventful pregnancy, we observed that the fetus repeatedly extended her index finger and "pointed" at the umbilical cord (fig ).